THE SPEECH RATE AND VOCABULARY PROFILE OF TED-ED VIDEOS AS EXTENSIVE LISTENING MATERIALS FOR EFL LEARNERS - Hidayati, Yustina; Suharyadi, Suharyadi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Listening proficiency is essential in language acquisition, yet both its classroom time and research are overshadowed by other skills, such as speaking and reading. To tackle the issue of limited classroom time, extensive listening is one of the most convenient and effective solutions. Selecting the materials, however, needs an equally extensive effort; especially for the authentic ones. Therefore, this study aims to investigate the speech rate and vocabulary level of TED-Ed videos as one of the sources of authentic material for extensive listening to determine their suitability for EFL learners. The research used a quantitative descriptive design with purposive sampling. The data collection of Speech Rate is conducted by transcribing the sample videos and dividing the number of words by the length of the video, and the result is measured in terms of WPM (Word Per Minute). To get the vocabulary level, the video transcripts are put into the Vocabkitchen website to analyze the vocabulary CEFR level for each word. From the analysis, the average speech rate of TED-Ed videos is 147.4 WPM and it is suitable for all levels of EFL learners, including beginner level. Meanwhile, the CEFR level of the vocabulary is more suitable for intermediate EFL learners and beyond.